Penyuluhan Manajemen Asuhan Kebidanan Pada Ibu Hamil Dengan Hipertensi Untuk Menurunkan Risiko Preeklampsia - Andi Hartati; Sahalia Sahalia; Cakrawati Cakrawati; Adisty Dwi Treasa (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Preeclampsia remains a leading cause of maternal morbidity and mortality in Indonesia. One of its main risk factors is hypertension during pregnancy that is not properly managed. This community service project aimed to improve knowledge and skills of pregnant women in managing midwifery care to prevent preeclampsia through educational counseling at Puskesmas X. The activity was conducted through preparation, implementation, and evaluation stages using an educational-participatory approach. A total of 30 pregnant women with mild to moderate hypertension participated. Counseling materials included recognition of preeclampsia warning signs, blood pressure monitoring, nutritional management, and home self-care. The evaluation results showed an increase in average knowledge score from 65.2 to 88.7 (a 23.5-point increase) and a 78% improvement in blood pressure measurement skills. This activity effectively enhanced pregnant women’s preparedness in preventing preeclampsia. Regular health education sessions by health workers are recommended to reduce pregnancy complications related to hypertension.